Introduction: On irreconciliation. (4th May 2022) - Mookherjee, Nayanika
Abstract: Most post‐conflict reconciliatory exercises make it incumbent upon survivors to forgive, and seek closure as a demonstration of 'moving on'. Various anthropologists have criticized reconciliation and related forms of 'alternative justice' extensively but within the framework of maintaining social bonds and the rule of law. In this introduction, I reflect critically on the interdisciplinary scholarship on reconciliation, apology, and forgiveness, and theorize irreconciliation as a less examined lens of analysis. Rather than being in opposition to 'peace', irreconciliation allows us to interrogate the status quo by refusing to forgive endemic impunities, particularly in the aftermath of staged processes of justice and the absence‐presence of the rule of law. In this special issue of the JRAI, I ethnographically explore irreconciliation's links with law, aesthetics, temporality, resistance, and control to locate its multiple analytical manifestations. Irreconciliation allows an important examination of the rule of law within processes of unresolved genocidal injustices and debates relating to slavery, Black Lives Matter, and institutional responses. Abstrait: Introduction : de l'irréconciliation Résumé La plupart des exercices de réconciliation engagés à l'issue d'un conflit imposent aux survivants de pardonner et de chercher une manière de résolution pour « aller de l'avant ». Divers anthropologues ont formulé des critiques de la réconciliation et des formes apparentées de « justice alternative », sans sortir du cadre du maintien des liens sociaux et de l'État de droit. Dans cette introduction, l'autrice pose un regard critique sur les travaux interdisciplinaires étudiant la réconciliation, l'excuse et le pardon, et elle théorise un prisme d'analyse moins usité : celui de l'irréconciliation. Au lieu de s'inscrire en opposition à « la paix », l'irréconciliation permet d'interroger le statu quo en refusant le pardon des impunités endémiques, notamment au terme de procédures judiciaires mises en scène et en l'absence‐présence de l'État de droit. Dans ce dossier, elle propose une exploration ethnographique des liens entre l'irréconciliation et le droit, l'esthétique, la temporalité, la résistance et le contrôle, afin d'en localiser les multiples manifestations analytiques. L'irréconciliation est un moyen important d'analyse de l'État de droit dans les procédures sur les injustices génocidaires irrésolues et les débats sur l'esclavage, Black Lives Matter et les réponses des institutions.